Системная трансформация посткоммунистических стран Центральной и Восточной Европы: российские и украинские исследования в ХХI ст. - Брусиловская [Brusylovskaya], Ольга [Olga] (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2018)
The research topic follows, firstly, from the fact that there is a need to examine the scientific schools of the 21st century. Secondly, the general tendency towards the re-ideologization of political science requires a critical interpretation of the state of affairs in the Russian Federation and Ukraine. Thirdly, in Ukraine and in the countries that are its allies, the theoretical analysis of historiography should be particularly helpful in offering a more clear definition of the former and current ideological positions of the aggressor country (the Russian Federation). The article compares the Russian and Ukrainian schools of political science, which have explored the impact on CEE of such actors as the EU, NATO, the USA, and Germany, as well as the economic, political, and ideological components of the systemic transformation.

Tematyka badawcza uwarunkowana jest przede wszystkim tym, że istnieje potrzeba studiowania szkół naukowych XXI wieku. Po drugie, ogólna tendencja do ponownej ideologizacji nauk politycznych wymaga krytycznej interpretacji stanu rzeczy w Federacji Rosyjskiej i Ukrainie. Po trzecie, w Ukrainie i krajach, będących jej sojusznikami, teoretyczna analiza dziejopisarstwa musi pomóc w szczególności wyraźniejszemu wyznaczeniu byłych i dzisiejszych światopoglądowych pozycji kraju-agresora (FR). W artykule porównuje się rosyjską i ukraińską szkołę politologii, które badały wpływ na region ESW takich czynników, jak UE, NATO, SZ i Niemcy, a także ekonomiczne, polityczne i ideologiczne składniki transformacji systemowej.

Тема исследования обусловлена, во-первых, тем, что существует пот- ребность в исследовании научных школ ХХI ст. Во-вторых, общая тенденция к реидеологизации политических наук нуждается в критическом осмыслении состояния вещей в РФ и Украине. В-третьих, в Украине и странах, являющих- ся ее союзниками, теоретический анализ историографии должен помочь в час- тности более четкому определению бывших и нынешних мировоззренческих позиций страны-агрессора (РФ). В статье сравниваются российская и украин- ская школы политологии, которые исследовали влияние на регион ЦВЕ таких факторов как ЕС, НАТО, США и ФРГ, а также экономическую, политическую, идеологическую составляющие системной трансформации.
Systemic Transformation of Post-Communist Countries in Central and Eastern Europe: Russian and Ukrainian Studies in the 21st Century
Transformacja systemowa krajów postkomunistycznych Europy Środkowej i Wschodniej: Studia rosyjsko-ukraińskie w XXI wieku
Keywords: CEE; systemic transformation; political science; Еuropa Środkowo-Wschodnia; systemowa transformacja; nauka polityczna; ЦВЕ; системная трансформация; политическая наука